A Study of the Entrepreneurial Constrains in the Indian Manufacturing Sector - Mohammad Ahmar Uddin; Khaliquzzaman Khan (International Journal of Economics and Financial Issues, 2015)
Promotion of entrepreneurship has been recognized world over as key to accelerate the economic development of a region. India also continues to take steps to directly or indirectly promote entrepreneurship. This paper attempts to find out the constraints being faced by entrepreneurs in the Indian manufacturing sector. For this study the entrepreneurs have been classified as per their gender, region, age and education. This study also highlights the steps that can be taken to overcome the various types of constraints being faced by such entrepreneurs.